AGING AND DISORDERS OF COGNITIVE PROCESSES IN OLD AGE AND GENERAL CLASSIFICATION OF COGNITIVE PROCESSES - Turdikulov Kamronbek Muzaffar o’g’li (PEDAGOGS, 2024)
Abstract: This article provides general information about aging and cognitive processes in people during this period, as well as brief and general information on cognitive processes.